Strong Bonding of Lattice N Activates Metal Ni to Achieve Efficient Water Splitting - Niandan Zhao; Wei Luo; Sijun Li; Hua Wang; Yini Mao; Yimin Jiang; Wenbin Wang; Ming Li; Wei Su; Rongxing He (Advanced Science, 2025)
Abstract Developing efficient and robust free‐standing electrocatalysts for overall water splitting is a promising but challenging task. Herein, the N‐incorporated Ni nanosheets non‐fully encapsulated by N‐doped carbon (NC) layer are fabricated (N─Ni©NC). The introduction of N not only regulates the size of nanosheets in N─Ni©NC but also promotes the electrochemical activity of metal Ni. Experimental and theoretical results reveal that strong bonding of the lattice N activates the inert metal Ni by promoting charge transfer between Ni and N. In addition, the upward shift of the d‐band center induced by lattice N enhances the adsorption of intermediates, thereby making Ni as a new OER active site together with C. This strategy of generating Ni and C dual active sites by introducing lattice N greatly accelerates oxygen evolution reaction (OER) kinetics, resulting in excellent electrocatalytic performance of N─Ni©NC. At the current density of 10 mA cm−2, the overpotentials of hydrogen evolution reaction (HER) and OER are 27 and 206 mV, respectively, and the cell voltage for overall water splitting only needs 1.47 V. This work offers a unique heteroatom activation approach for designing free‐standing electrodes with high activity.